Synthesis of Fe(3)O(4)/Ag nanohybrid ferrofluids and their applications as antimicrobial and antifibrotic agents - Taufiq, Ahmad (Heliyon, 2020)
To date, the search for creating stable ferrofluids with excellent properties for biomedical application is one of the challenging scientific and practical investigations. In this study, novel Fe(3)O(4)/Ag nanohybrid ferrofluids from iron sand were synthesized using a double-layer method. The Fe(3)O(4)/Ag nanocomposites exhibited stable crystallite sizes of 11.8 12.1 nm and 36.8–37.2 nm for Fe(3)O(4) and Ag, respectively. The lattice parameters of the spinel structure Fe(3)O(4) and face-centered cubic Ag were respectively 8.344 Å and 4.091 Å. With increasing Ag amount, the crystallite phase of Ag in the nanocomposites increased from 40.2% to 77.2%. The XPS results confirmed that Fe(3)O(4)/Ag nanocomposites were successfully prepared, where Fe(3)O(4) mixed well with Ag via strong ionic bonding. The FTIR results confirmed the presence of Fe(3)O(4)/Ag, oleic acid, and dimethyl sulfoxide as the filler, first layer, and second layer, respectively. The as-prepared ferrofluids exhibited superparamagnetic behavior, where the saturation magnetization decreased with increasing Ag content. The Fe(3)O(4)/Ag nanohybrid ferrofluids exhibited excellent antimicrobial performance against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Candida albicans. More importantly, the Fe(3)O(4)/Ag nanohybrid ferrofluids decreased the progression of liver fibrosis-related inflammation and fibrogenic activity on hepatic stellate cells.